EUROPE ELECTRONIC DATA INTERCHANGE (EDI) AGREEMENT DAN ELECTRONIC COMMERCE (ECE) AGREEMENT - Gunawan Widjaja; Andreani Dewanto; Monica Monica; Hendrawan Hendrawan; Melyana Melyana (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
EDI is a process of transferring business data/documents electronically between several machines within an organization in a format that can be recognized on each of these machines. One example of using EDI is that when we transact online via a computer, we will submit an order and the computer system from there will reply to it with an invoice for our total shopping. EDI has standardized the coding of trade transactions, so that commercial organizations can communicate directly from one computer system to another without the need for hardcopy, invoices, and avoid delays, unintentional errors in file handling and human intervention.